PENGARUH LATIHAN CUTTING DRILLSTERHADAP KELINCAHAN PEMAIN SEPAKBOLA BINATAMA FC U-16 BENGKALIS - Alhafis, M. Julianda Alhafis; Agust, Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT :Thisresearch wasconducted to determinewhetherthere was an effectof exerciseCutting Drillsto improve agility oftheBINATAMA FC U-16playersBengkalis, so that when the motion change rapidly, making the opposing players cheated and irrespective of custody. The kind ofthis research istheexperimental, the populationin this studywas aBINATAMA FC U-16playersBengkalis, the samplein this studyis BINATAMA FC U-16playersBengkalisactivein training, amounting to 18 players. The sampling techniquethat isnon-random sampling.Non-random samplingis asamplingprocessthat is not basedonrandomization. Inthisstudyresearchers used apurposive sampling technique. Purposive samplingis asamplingof the researcherpointed directlywho willbesampledinthe study, butthe selectionbasedonthe specificobjectivesofthe research conducted. Researchersconsider thesuitability ofa problemwith theselected individuals. The instrumentsused in this researchis theIllinoistAgilityRunTest, whichaimstomeasure theagilityof movement. After that, the datais processedwith statistics, normalityused lilifors test at a significan 0,05α. The hypothesis isthe effectof exerciseProAgilityShuttleAgainstAgility. Based ont test analysisproducesTaccountof 12.89andTtabel1,740, meansTaccount>Ttable. Based on theanalysis ofstatistical data, there arean averageof17.21 andPree-test averagepost-testat16.65, then the data isnormal. Thus, there isthe effect ofexerciseCutting DrillstotheBINATAMA FC U-16playersBengkalis. Keywords: Cutting Drills, Agility